The death penalty : an American history - Banner, Stuart, 1963- (Harvard University Press, 2002)
A comprehensive account of the death penalty in the United States. Stuart Banner tells the story of dramatic changes, over four centuries, in the ways capital punishment has been administered and experienced. In the seventeenth and eighteenth centuries, death was the standard penalty for a laundry list of crimes--from adultery to murder, from arson to horse- theft. Hangings were public events, staged before enormous audiences, attended by women and men, young and old, black and white. Early on, the gruesome spectacle was an explicitly religious event--replete with sermons, confessions, and last-minute penitence--to promote the salvation of both the condemned person and the spectators. Through the nineteenth century, in response to changing mores, execution became increasingly secular and private. In the twentieth and twenty-first centuries, as execution has become a quiet, sanitary, technological procedure, the death penalty is as divisive as ever. Re-creating what it was like to be the condemned prisoner, the executioner, and the eyewitness, Banner moves beyond the debates to give us an understanding of America's ultimate punishment.